2014
DOI: 10.1186/1880-5981-66-72
|View full text |Cite
|
Sign up to set email alerts
|

Frictional properties of sediments entering the Costa Rica subduction zone offshore the Osa Peninsula: implications for fault slip in shallow subduction zones

Abstract: We examined the frictional properties of sediments on the Cocos plate offshore the Osa Peninsula, Costa Rica, and explored variations in the intrinsic frictional properties of the sediment inputs to the Costa Rica subduction zone. Sediment samples were collected at Site U1381A during the Integrated Ocean Drilling Program Expedition 334, and include hemipelagic clay to silty clay material (Unit I) and pelagic silicic to calcareous ooze (Unit II). The frictional properties of the samples were tested at a normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…11; Table 3). Namiki et al (2014) found that the Site U1381 unit I composed of clay and silty clay is significantly weaker (µ = 0.13-0.16) compared to the underlying siliceous and calcareous oozes (µ = 0.63-0.77). Kurzawski et al (2016) reported the friction coefficient of the clay and silty clay of unit I at Site U1414 to be µ = 0.56; this is significantly lower than that of the calcareous nannofossil ooze of unit IIB (µ = 0.84) but higher than Namiki et al's (2014) values for the corresponding unit, although still lower than their values for the ooze.…”
Section: Friction Of Costa Rica Inputsmentioning
confidence: 98%
See 1 more Smart Citation
“…11; Table 3). Namiki et al (2014) found that the Site U1381 unit I composed of clay and silty clay is significantly weaker (µ = 0.13-0.16) compared to the underlying siliceous and calcareous oozes (µ = 0.63-0.77). Kurzawski et al (2016) reported the friction coefficient of the clay and silty clay of unit I at Site U1414 to be µ = 0.56; this is significantly lower than that of the calcareous nannofossil ooze of unit IIB (µ = 0.84) but higher than Namiki et al's (2014) values for the corresponding unit, although still lower than their values for the ooze.…”
Section: Friction Of Costa Rica Inputsmentioning
confidence: 98%
“…For the input Site 1039 offshore Nicoya Peninsula, friction data were reported by Kopf (2013) for (effective) normal stresses of 4-15 MPa and slip rates of 0.01-100 µm/s. Namiki et al (2014) sheared samples from the Osa Peninsula input Site U1381 at 5 MPa normal stress and slip rates of 2.8-280 µm/s. Studies by Ikari et al (2013b) for Sites 1039 and 1253 and by For the Nicoya input sites, the Site 1039 unit U1B diatom ooze with ash exhibits slightly lower friction coefficient values (µ = 0.28-0.34) compared to the underlying siliceous and calcareous oozes (µ = 0.40; Kopf, 2013) ( Fig.…”
Section: Friction Of Costa Rica Inputsmentioning
confidence: 99%
“…A. Tsutsumi built an IHV friction apparatus at Kyoto University with capabilities of v = 5 lm/s to 4.6 m/s and normal stress r n to 20 MPa for specimens of 40 and 15 mm in outer and inner diameters, respectively (#5 in Table 1). The apparatus was used for studying the behavior of gouge from accretionary prism Ujiie and Tsutsumi 2010;Ujiie et al 2011;Saito et al 2013;Namiki et al 2014), hydrated amorphous silica formation along a fault in chert (Hayashi and Tsutsumi 2010), and J-FAST drill core in Japan trench (Ujiie et al 2013). A. Lin installed a LHV apparatus with two specimen assemblies including one with a pressure vessel at Shizuoka University (now moved to Kyoto University; v = 0.6 m/a to 1.3 m/s, r n to 200 MPa for specimens of 25 mm in outer diameter), and applied it to dehydration and melting of serpentinite at seismic slip rates (#6 in Table 1; Lin et al 2013).…”
Section: Friction Apparatuses and Research Outcomesmentioning
confidence: 99%
“…(1)The Nankai trough (14 papers; Sugihara et al 2014, Tsuji et al 2014, Idehara et al 2014, Akuhara and Mochizuki 2014, Hyodo et al 2014, Takahashi et al 2014, Yamada and Shibanuma 2015, Takeshita et al 2014, Hino et al 2015, and Toki et al 2014) (2)The Japan trench (6 papers; Aochi and Ide 2014, Koge et al 2014, Sawai et al 2014, and Boston et al 2014) (3)Other trenches and fault zones (4 papers; Maekawa et al 2014, Namiki et al 2014) and ancient accretionary complexes and faults on land (7 papers; Schumann et al 2014, Hamahashi et al 2015, Kogure et al 2014, and Hashimoto and Yamano 2014) (4)Theoretical treatments of fracture and earthquake (2 papers; Kame et al 2014 andNishiyama et al 2014) The papers are also categorized into three scientific issues, focusing on different regions within each topic:…”
mentioning
confidence: 99%
“…(1)Framework and setting of the seismogenic zone from the view point of seismicity in the Nankai trough (Idehara et al 2014, Akuhara andMochizuki 2014), Japan Trench (Aochi and Ide 2014), Hikurangi margin , or from the geological and geophysical points of view for the Nankai Trough (Tsuji et al 2014, Sugihara et al 2014) and Japan Trench (Boston et al 2014, Koge et al 2014) (2)Material and physical properties or conditions of the fault for the Nankai Trough (Takahashi et al 2014, the Japan Trench (Sawai et al 2014), and the Costa Rica margin (Namiki et al 2014) (3)Analysis of water-rock interaction with faulting in an ancient accretion complex and fault in the Shimanto Belt, Japan (Schumann et al 2014, Hamahashi et al 2015, Chelunpu Fault, Taiwan , Alaska , Median Tectonic Line, Japan , crustal rocks on land (Kogure et al 2014), and theoretical treatment of fracturing, friction, and earthquakes (Nishiyama et al 2014, Kame et al 2014 Traditional research on earthquakes is physics-based, but physico-chemical processes and their geological record in fault rocks, both in active and inactive fossilized rocks, are of recent concern. Many studies of natural records of seismic faulting have been conducted in terms of their physico-chemical processes.…”
mentioning
confidence: 99%